ANDROGEN PARTICIPATION IN THE ADAPTATION OF MYOFIBRES AND EXTRACELLULAR MATRIX OF RAT SKELETAL MUSCLES TO ENDURANCE TRAINING - S. Delchev; F. Gerginska; K. Georgieva (Trakia Journal of Sciences)
The PURPOSE of the present study was to investigate the changes in the size of skeletal muscle fibres and extracellular matrix (ECM) after submaximal training and androgen receptor blocker (ARB) treatment. METHODS: Two groups of animals were used: trained (T) and non-trained (NT). Half of the trained (T+F) and untrained (NT+F) rats were treated with the ARB Flutamide. RESULTS: The analysis of the muscle fibre cross-sectional areas (CSA) of soleus (Sol), extensor digitorum longus (EDL) and gastrocnemius (Gas) showed that trained rats had larger CSA than non-trained. ARB application significantly reduced CSA of EDL and Gas in the trained animals. ARB had no effect of on the amount of ECM in Sol and EDL after training, while in Gas the amount was greater than in the trained controls. CONCLUSIONS: The reduction in the CSA of EDL and Gas muscle fibres is probably due to the higher content of type II fibres, which are more sensitive to androgens. The unchanged amount of ECM in Sol and EDL of the ARB-treated and trained rats suggested a lack of androgen effect. The ECM remodelling in Gas following endurance training is androgen-dependent.